DEVELOPMENT PUZZLE GAME APPLICATIONS USING VISUAL BASIC PROGRAMMING LANGUAGE 6.0 - JAMRONI author; Elly Agustina J., SKom, MMSI (Jurnal Sistem Informasi, 2004)
Game (game) Puzzle is a type of game that has kind of pieces with complex shapes, so long as players try to match the pictures, players must match the form of connection. Starting from the type of puzzle pieces totaling keeping teens, making a total of tens and even hundreds of copies. Display images vary Puzzle to add charm. For example one image display Akane Kanazawa Japanese artist, there are also display images Grand_Canyon famous waterfalls such, and the spider superhero is Spiderman. Make a game program (game) Puzzle can also add appeal creativity of children, besides that also children can recognize and learn the computer.